The effect of ascorbic acid on the retention of calcium in normal adult women - Higano, Shizuko, author; Dyar, Elizabeth, advisor; Stiminel, Margaret P., committee member; Washburn, L. E., committee member; Bourne, Richard F., committee member (Colorado State University. Libraries, 1944)
To view the abstract, please see the full text of the document.
Keywords: Vitamin C -- Physiological effect; Calcium in the body